An Introduction to Sequence Similarity ("Homology") Searching. Issue 1 (1st June 2013) - Pearson, William R.
Abstract: Sequence similarity searching, typically with BLAST, is the most widely used and most reliable strategy for characterizing newly determined sequences. Sequence similarity searches can identify "homologous" proteins or genes by detecting excess similarity— statistically significant similarity that reflects common ancestry. This unit provides an overview of the inference of homology from significant similarity, and introduces other units in this chapter that provide more details on effective strategies for identifying homologs. Curr. Protoc. Bioinform . 42:3.1.1‐3.1.8. © 2013 by John Wiley & Sons, Inc.